Dark solitons impinging on interfaces in a superfluid Fermi gas - Merckx, Jannes; Tempere, Jacques (Frontiers in Physics, 2022)
Ultracold quantum gases in the superfluid regime exhibit solitons, localized excitations that require nonlinearity of the underlying field equation in order to preserve their shape as they propagate. Solitons are well understood in a uniform system, but recent advances in trapping and manipulating superfluid quantum gases allow to study how these objects interact with inhomogeneities. Here, we look at a particular type of inhomogeneity: an interface that separates two different interaction regimes of a superfluid Fermi gas, close to unitarity. It is known that the soliton properties depend on the interaction regime, but what happens as a soliton impinges on such an interface is not clear. Using an effective field theory to describe the superfluid Fermi gas, we reveal the nontrivial dynamics of such a collision. Whether the original soliton makes it through the interface depends on the interaction strength and density of the superfluid behind the interface. Regardless of whether the original soliton is transmitted or not, there will always be a shock wave with a phonon train created behind the interface. The reflected part of the soliton breaks up into smaller solitons. The details of this dynamics depends strongly on the equation of state corresponding to underlying microscopic theory describing the superfluid Fermi gas, and we argue that these collisions are realistic experimental probes to test microscopic theories of pairing in ultracold Fermi gases.